2021
DOI: 10.1007/s10854-021-06430-3
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric and structural properties of bismuth sodium potassium titanate lead-free ceramics for energy harvesting

Abstract: The development of bulk piezoelectric ceramics with high energy conversion efficiency is of decisive importance for the requirements of the advanced energy harvesting devices toward miniaturization and integration. There is an additional motivation in the piezoelectric ceramics, lead titanate-zirconate (PZT) ceramics are the most widely used energy harvesting (EH) materials. This fact is important because legal restrictions on the use of lead in electronic devices have led to greater efforts being made to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Recently Camargo et al investigated the lead-free BNKT piezoceramic, and showed that higher piezoelectric properties ( d 33 = 129 pC N −1 and d 31 = 12.8 pC N −1 ) and an output voltage of 19.9 V g −1 were achieved, and that these materials can be successfully applied as energy harvesters instead of lead-based toxic materials. 186…”
Section: Poling Influence On Lead-based Ceramics Lead-free Ceramics P...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Camargo et al investigated the lead-free BNKT piezoceramic, and showed that higher piezoelectric properties ( d 33 = 129 pC N −1 and d 31 = 12.8 pC N −1 ) and an output voltage of 19.9 V g −1 were achieved, and that these materials can be successfully applied as energy harvesters instead of lead-based toxic materials. 186…”
Section: Poling Influence On Lead-based Ceramics Lead-free Ceramics P...mentioning
confidence: 99%
“…Using the desired orientation of the domain ) and an output voltage of 19.9 V g À1 were achieved, and that these materials can be successfully applied as energy harvesters instead of lead-based toxic materials. 186 In BNT materials, texturing is achieved via the reactivetemplated grain increment process, using particles such as Na 0. NBiT or BiT particles into templates of pure-phase BNT.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The development of piezoelectric materials with high energy conversion efficiency is of decisive importance for the requirements of advanced energy harvesting (EH) devices toward miniaturization and integration. 2 Lead titanate zirconate (PZT) ceramics are the most widely used energy harvesting materials due to their excellent piezoelectric properties, 3 i.e. , high mechanical quality factor ( Q m ), high piezoelectric constant ( d 33 ), and large planar electromechanical coupling factor ( k p ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have identified many possible lead-free candidates based on barium titanate (BaTiO 3 , BT), potassium sodium niobates (K 0.5 Na 0.5 NbO 3 , KNN), bismuth sodium titanates (Bi 0.5 Na 0.5 TiO 3 , BNT), bismuth potassium titanates (Bi 0.5 K 0.5 TiO 3 , BKT), and bismuth layered ferroelectrics. 2,5 Among them, BNT has been found to be a possible energy storage material due to its high spontaneous polarization ( P m ) exceeding 40 μC cm −2 , which results from the hybridization of the Bi 6p and O 2p orbitals. 6 Nevertheless, a pure BNT ceramic is known to be to be sintered with difficulty, and it also has other issues, such as beginning polarized with just as much complication, not to mention its having a high coercive field ( E c ), high conductivity, and poor temperature stability.…”
Section: Introductionmentioning
confidence: 99%